Effects of DLC/TiAlN-coated die on friction and wear in sheet-metal forming under dry and oil-lubricated conditions: Experimental and numerical studies - Sulaiman, Mohd Hafis; Ramli, Nur Farahana; Bienk, K; Nielsen, Chris Valentin; Bay, Niels (Elsevier Ltd, 2019)
Experimental and numerical analyses were conducted to explore the influence of DLC/TiAlN-coated die surfaces in sheet-metal forming under dry and oil-lubricated conditions. In this study, ironing and deep-drawing experiments were performed to determine the potential of the DLC/TiAlN coating in the sheet forming of stainless steels under different tribological conditions. The performance and physical properties of the DLC/TiAlN-coated die surface were obtained through load, surface roughness, and wear measurements as well as hardness and microstructure examination. The experimental results indicated that the DLC/TiAlN coating strongly resists galling under dry friction and thin film lubrication conditions that reduces the friction and forming load. The presence of a thin oil film reduces the sliding-originated surface tensile stresses of the DLC/TiAlN coating, improving the wear resistance of the die surface even at high temperatures and high contact pressures. Thermomechanical numerical analysis supported the experimental results, which confirmed that the lubricant discharged the heat generated in the die–workpiece contact region to reduce the friction and forming load. With the DLC/TiAlN coating, the plain mineral oil with no extreme pressure additives can function as effective as chlorinated paraffin oil for protecting the die surface, thus extending the die service life.